Ecological interdependencies and resource competition: The role of information and communication in promoting effective collaboration in complex management situations. - Bodin, Örjan (Stockholm University, 2019)
Communication between resource users has repeatedly been shown to be of significant importance in environmental management. The proposed causal mechanisms are numerous, ranging from the ability of users to share information to their ability to negotiate solutions to common problems and dilemmas. However, what is less known is under what conditions these potential causal mechanisms are important and if, in cases when different means other than communication were available, whether they would be more effective in accomplishing these objectives. An example of such an alternative could be that instead of (or in addition to) users being reliant on within-group communication to acquire useful information an intermediary - such as a public agency - could provide that for them. Furthermore, the different causal mechanisms making communication beneficial might not be independent, neither in respect to each other, nor in respect to other externally imposed means to facilitate better environmental management, and not in regards to different contextual factors. This study makes use of laboratory experiments in an innovative way to explore these questions and specifically test the relative importance of communication in managing complex social-ecological system characterized by common-pool resource dilemmas, ecological interdependencies, and asymmetric resource access – all characteristics being present simultaneously. We find that when resources users are confronted with such a complex challenge, the ability to communicate significantly increases individual and group performance. What is more surprising is the negative effect on overall outcomes that providing external information has on outcomes, when the users also have the ability to communicate. By analysing the content of the conversations we are able to suggest several possible explanations on how the combination of external information provisioning and user communications act to increase individual cognitive load and drives intra-group competition, leading to a significant reduction of individual and group outcomes.

Behavioural experimental results, per round for the different treatments. All messages are coded (see published paper)

Studien har undersökt hur personer interagerar i samband med att de ställs inför utmaningen att hantera komplicerade naturresurser. Studien använder sig av en innovativ experimentell metod för att testa den relativa vikten av kommunikation i hanteringen av komplexa social-ekologiska system som kännetecknas av dilemma i förvaltningen av gemensamma resurser.

Behavioural experimental results, per round for the different treatments. All messages are coded (see published paper)
Ecological interdependencies and resource competition: The role of information and communication in promoting effective collaboration in complex management situations.
Keywords: Administrative units; Administrativa enheter; common-pool resources; allmänning; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Social Sciences; Samhällsvetenskap; Environment; Miljö